The role of TripAdvisor in influencing travellers' decision making / Ahmad Izzat Ismail, Nur Ain Ishak and Nurul Amieza Abd. Talip - Ismail, Ahmad Izzat; Ishak, Nur Ain; Abd. Talip, Nurul Amieza (2014)
TripAdvisor is the world's largest travel community pioneering the Web 2.0 travel revolution. TripAdvisor were among the highly sought-after medium of information gathering regarding travel products. It offers the real advice from real travellers and lots of features to help travellers plan and share their holiday. The goal of this study is to investigate on the role of TripAdvisors in travellers' decision in deciding their travel destinations. The main focus was on the three attributes which are features, speed and Electronic word-of-mouth (e-WOM) as it influences travellers' decision making. By analyzing each of the attributes, the researchers produced some interesting findings, which have important in improving the travel websites. A total one hundred (100) travellers were investigated by a structured questionnaire which consists of three (3) sections. The sections were demographic profile, attributes of TripAdvisor and travellers' decision making. From the analysis of data, the most agreeable attributes were identified in the findings of this research. Finally, some recommendations are proposed for the TripAdvisor and others online travel sites to focus on the others perspective that can contribute on traveller’s convenience in accessing the websites.